Produção de L (+)-ácido lático por Lactobacillus casei Ke11 utilizando insumos agroindustriais - Oliveira, Paola Monteiro de [UNESP] (2014)
The lactic acid is a organic acid widely used in various industry sectors but currenty has received great interest since it can be used in the production of renewable and biodegradable plastics made from polylactic (PLA). Moreover, it can be bioresorbable, PLA biopolymers can be used in medicine, tissue regeneration, sutures, fixation of fractures, bone replacement, repair cartilage, ligament fixation and implants. In this paper three carbon sources (sucrose PA, sugarcane juice and cheese whey) and four nitrogen sources (corn steep liquor – CSL, yeast autolyzade, yeast extract and cottonseed meal -Pro-floo®) were analyzed for the L(+)- lactic acid production by Lactobacillus casei Ke11. A completely randomized design was used in 3x4 factorial with four replications. The results were then subjected to analysis of variance by F test and the means were compared by Tukey test at 5% probability. When the sucrose and yeast extract were used great results of L(+)-lactic acid production and yield were obtained (87,09 g/L and 88%, respectively). The Plackett-Burman planning was performed with the variables sucrose, yeast extract, percentage of inoculum, potassium phosphate, magnesium sulfate, manganese sulfate, sodium acetate, citrate and Tween 80. Tha variables that increase the L(+)-lactic acid production were the yeast extract, percentage of inoculum and Tween 80. A rotational central composite experimental design (DCCR) was made by using these three significant variables and sucrose, then is possible to conclude by observing the response surfaces that to obtain a greater amount of L(+)-lactic acid production and a smaller amount of residual sucrose the parameters of sucrose, yeast extract and percentage of inoculum should be 120 g/L, 40 g/L and 10%, respectively. The validation of the optimized medium was carried out in a shaker fermentation and the values obtained were: 112, g/L of L(+)-lactic acid production, 4,76 g/L/h of productivity and...